Acute effects of rope jumping warm-up on power and jumping ability in track and field athletes - Makaruk, H. (Polish Journal of Sport and Tourism, 2013)
The purpose of this study was to compare the acute effects of traditional jumps and rope jumps during warm-up on power and jumping ability in trained men. Material and methods. A group of 12 national-level track and field athletes participated in the study. Peak power and jumping ability were assessed by having participants perform five alternate leg bounds, a countermovement jump (CMJ) and a drop jump (DJ). Three different warm-up protocols were used in random order, with 3-day intervals between them. The first involved traditional jumps, the second rope jumps and the control consisted of general warm-up only (jogging and stretching). Results. The rope-jump warm-up protocol significantly improved jumping distance (p<0.05) as compared to the traditional protocol. There were no significant differences in peak power or jump height among experimental groups in the CMJ and DJ. The study also revealed that traditional and ropejump protocols significantly (p<0.001) increased peak power and jump height for the CMJ and DJ, and jump distance for the five alternate leg bounds compared to the control condition. Conclusion. The results of this study suggest that a warm-up including rope jumps may be more effective for horizontal jumping tasks than a protocol with traditional jumps, and that traditional and rope-jump warm-up protocols provide similar levels of enhancement for vertical jumping tasks.